En osynlig risk - Palmer, Sofia (2008)
Approximately 400 people in Sweden die each year by lung cancer caused by radon gas. Authorities have in recent years invested big resources and organized campaigns to encourage people to take action against high occurrence of radon in residences. With low frequency of applications for radon allowances as the main measure, a lot interprets on a very low commitment. The purpose of this thesis is to investigate the reasons for the low commitment among people. The study is based on a questionnaire survey sent to 444 house owners in Uppsala. Clearly visible in the result is that many do not see radon as an alarming health risk, which directly leads to passivity in carrying out measures. Anxiety in order to costs associated with measures will become very high is yet another contributing reason for postponing the measurements to the future. There are also underlying reasons to the low commitment; for example due to a variety of psychological causes common people do not look as serious at the risk of radon compared to the authorities. The conclusion is that common people experiences insufficient reasons to deal with high radon occurrence.